Synthesis and Applications of Cyclopropanones and Their Equivalents as Three-Carbon Building Blocks in Organic Synthesis - Jang, Yujin; Machín-Rivera, Roger; Lindsay, Vincent N. G. (Synthesis, 2021)
Cyclopropanone derivatives constitute highly strained cycloalkanones with promising applications as three-carbon building blocks in organic synthesis. Due to the presence of a ketone in such a small ring system, all C–C bonds and the carbonyl group are considered to be labile in suitable conditions, leading to a wide variety of synthetic disconnections, including nucleophilic addition, ring expansion, ring-opening, and (formal) cycloaddition. Despite their synthetic potential, the widespread adoption of cyclopropanones as substrates has been considerably hampered by the difficulties associated with the preparation and storage of such unstable compounds, prompting the development of cyclopropanone surrogates that can equilibrate to the parent ketone in situ via elimination. This review summarizes the syntheses and applications of cyclopropanone derivatives and their equivalents, and offers a perspective of the state of the field as well as its expected future directions.1 Introduction2 Preparation of Cyclopropanones and Their Equivalents2.1 Carbenoid Chemistry2.2 Allene Oxide Rearrangement2.3 Ring Closure by Dehydrohalogenation or Dehalogenation2.4 Photolytic Processes2.5 Miscellaneous Formation of Cyclopropanones2.6 Cyclopropanone Equivalents3 Synthetic Applications of Cyclopropanones and Their Equivalents3.1 Nucleophilic Addition to the Carbonyl Group3.2 Ring Expansion3.3 Ring-Opening3.4 Cycloaddition and Formal Cycloaddition4 Conclusion and Outlook
Keywords: cyclopropanone; ring strain; oxyallyl; Favorskii; homoenolate; ring expansion; ring opening